2021
DOI: 10.33907/turkjes.771896
|View full text |Cite
|
Sign up to set email alerts
|

Okul Öncesi Öğretmenlerinin Sınıf İçi Fen Uygulamalarına Yönelik Tutumu Ve Uygulama Analizi

Abstract: Bireylerin dünyayı anlayabilmeleri ve uyum sağlayabilmeleri için okul öncesi dönem kritik bir öneme sahiptir. Okul öncesi eğitimde çocuklar araştırarak, yaparak yaşayarak, bilginin farkına varmayı, bilgiyi kullanmayı ve geliştirmeyi öğrenirler. Bu çalışmada okul öncesi öğretmenlerinin fen eğitimine yönelik tutumları, sınıf içinde kullandıkları yöntem-teknikler ve sınıf içi aktiviteleri kullanım oranları incelenmiştir. Araştırma yöntemi nitel ve nicel veriler kullanılarak karma modelle oluşturulmuştur. Araştırm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
1
1
0
1
Order By: Relevance
“…In the sub-theme "For organising the environment", it was determined that teachers used the science centre and sensory centre as science activities (Childinitiated open-ended science learning experiences). Similar to the results of this study, in other studies, preschool teachers stated that they mostly conducted experiments, observations and nature study activities (Akcanca et al, 2017;Polat et al, 2021;Simsar et al, 2017). The results of the studies and the results of this study show that observation, investigation and experimentation activities are frequently preferred by teachers within the scope of science studies in preschool period.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In the sub-theme "For organising the environment", it was determined that teachers used the science centre and sensory centre as science activities (Childinitiated open-ended science learning experiences). Similar to the results of this study, in other studies, preschool teachers stated that they mostly conducted experiments, observations and nature study activities (Akcanca et al, 2017;Polat et al, 2021;Simsar et al, 2017). The results of the studies and the results of this study show that observation, investigation and experimentation activities are frequently preferred by teachers within the scope of science studies in preschool period.…”
Section: Discussionsupporting
confidence: 86%
“…Teachers' lack of self-confidence and knowledge about science (Gerde et al, 2018;Park et al, 2017), their inability to allocate enough time for science activities (Greenfield et al 2009, Park et al, 2017, and their inability to use materials effectively (Tu, 2006) have been shown among the factors that hinder science education. Similarly, in studies conducted in Turkey, it has been reported that preschool teachers do not use different methods, techniques and materials (Karamustafaoğlu & Kandaz, 2006;Yıldız & Tükel, 2018), have difficulties in providing suitable materials (Babaroğlu & Okur Metwalley, 2018;Ültay et al, 2018); they do not have the necessary competencies related to science (Aslan et al, 2015;Karaer & Kösterelioğlu, 2005), they do not make children active in experimental activities (Polat et al, 2021), and they do not provide children with problem-solving opportunities (Gündüz & Akduman, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…İlgili literatür incelendiğinde, okul öncesi fen eğitiminde öğretmenlerin tercih ettikleri yöntemlerin başında deneyin geldiği görülmektedir (Akcanca, Aktemur Gürler ve Alkan, 2017;Dağlı, 2014;Dağlı ve Dağlıoğlu, 2020;Günay Bilaloğlu, Aslan, ve Aktaş Arnas, 2008;Kallery ve Psillos, 2002;Karamustafaoğlu ve Kandaz, 2006;Orhan, 2019;Özbek, 2009;Polat, Zengin, ve Elmalı, 2021;Simsar ve Doğan, 2019;Ültay, Ültay, ve Çilingir, 2018;Yıldız ve Tükel, 2018). Öte yandan, öğretmenlerin okul öncesi fen eğitiminde deneyi nasıl kullandıklarına dair bir bulguya ulaşılmamıştır (Yılmaz, Özen-Uyar ve Dikici-Sığırtmaç, 2020).…”
Section: Introductionunclassified